2016
DOI: 10.18051/univmed.2015.v34.213-219
|View full text |Cite
|
Sign up to set email alerts
|

Frailty decreases physical health domain of quality of life in nursing home elderly

Abstract: BACKGROUNDApproximately 10-27% of the population aged >65 years suffers from frailty. The percentage increases with age so that the prevalence of frailty in the population aged >85 years reaches 45%. The objective of this study was to determine the relationship between frailty and quality of life (QOL) in nursing home elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Few studies have evaluated the relationship between frailty and Quality of life among general aged care home residents [22,23,24,25,26]. There exists no study focusing on a target population of aged care home residents taking CNS medications and reporting the relationship between frailty and medication appropriateness from a Malaysian perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated the relationship between frailty and Quality of life among general aged care home residents [22,23,24,25,26]. There exists no study focusing on a target population of aged care home residents taking CNS medications and reporting the relationship between frailty and medication appropriateness from a Malaysian perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was calculated using planned proportion at a 95% confidence level to achieve a 5% margin of error, with previous frailty prevalence in Indonesia of 52.2%. 6 After obtaining permission from the head of home care and written informed consent signed by the respondents, the respondents were recruited. Respondents with physical and mental limitations were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…4 A systematic review reported the prevalence of frailty and pre-frail in the community of 10.7% and 41.6%, respectively 5 whereas a study in Indonesia reported the prevalence of frailty was 52.2%. 6 Frailty increases the risk of premature death, falls, fractures, dementia which impair quality of life therefore, increasing health care cost. 7 A study in Germany has shown a relationship between an increase in the frailty index and an increase in health care costs.…”
Section: Introductionmentioning
confidence: 99%